Telenursing practice in the care of patients with surgical cancer: a scoping review - Carla Aparecida do Nascimento Mozer; Juliana do Carmo Gonçalves; Lorena Barros Furieri; Mirian Fioresi; Cindy Medici Toscano Rozetti; Rachel de Carvalho; Bruno Henrique Fiorin (BMJ Open)
Objectives Surgical oncology patients often experience doubts and uncertainties in the preoperative and postoperative periods, which can be addressed remotely through telenursing. Expanding telenursing services could contribute to more comprehensive perioperative care. We conducted a scoping review to characterise these telenursing services, identify their outcome indicators and examine the content of the care delivered.Design A scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) recommendations.Data sources MEDLINE (PubMed), EMBASE, CINAHL, SCOPUS, Web of Science and Virtual Health Library (VHL), with searches performed up to 5 May 2025.Eligibility criteria for selecting studies We included studies that implemented telenursing interventions in the preoperative or postoperative period in adult oncology patients.Data extraction and synthesis Two independent reviewers used a standardised search to select and extract data from the included studies. Study characteristics were presented descriptively using absolute and relative frequencies, and the content of telenursing interventions was organised into a circular thematic matrix.Results A total of 37 studies were included, published between 1996 and 2024, conducted in 12 countries and primarily focused on postoperative telenursing via telephone or video calls. Preoperative care focused on psychosocial support and guidance related to surgical preparation. Postoperative topics included surgical wound care; handling of devices such as drains, ostomy bags and catheters; instructions for returning to work and support groups for financial and social assistance. Outcome indicators were primarily related to care, including levels of anxiety, stress, depression and quality of life.Conclusions Oncologic surgical telenursing remains primarily focused on postoperative care and the delivery of personalised support. Reporting on the protocols used, frequency and duration of sessions, nurse training and profiles, integration with in-person care workflows and operational cost data could strengthen the knowledge base for perioperative telenursing in oncology.